Quality assessment for large-aperture optical elements inducing phase jumps - Vicenţiu Iancu; Anda-Maria Talpoşi; Cristina Gheorghiu; Răzvan Ungureanu; Ioan Dăncuş; Dan-Gheorghiţă Matei; Daniel Ursescu (High Power Laser Science and Engineering)
Achieving complex pulses with high-power lasers necessitates rigorous testing of specially designed optical components. The qualification of these components using complementary devices to access both the high-resolution and the large-aperture properties, followed by validation using propagation simulations, is proposed here. In particular, the topology of a large-aperture staircase-like Fresnel phase plate used to generate vortex pulses is qualified using a non-contact optical profiler and a large-aperture wavefront measurement setup based on a Shack–Hartmann sensor. The resulting topography is further used for simulating the focus of laser beams after passing through the phase plate. Step height distribution effects on the doughnut-shaped focus are identified, and avoiding the indicated pitfall in the design of the phase plate provides at least a 10-fold reduction of the irradiance modulation on the circumference of the focus in the super-Gaussian case.